The Qualitative and Quantitative Analysis of Fruit of Acacia nilotica - Kamble, Ashwini; Kadav, Shraddha; Shinde, Pradnya; Tamboli, Ashpak (Indian Journal of Integrative Medicine, 2023)
The objective of this study is to enlighten readers about the phytochemicals found in Acacia nilotica trees. The acacia nilotica species, often called as "Babul" or "Kikar," is widely distributed in tropical and subtropical regions. Acacia nilotica is a significant, multifunctional medicinal plant that has been used to cure a variety of diseases. It is a member of the fabaceae family. The goal of this work is to identify the phytochemicals in the hydroalcoholic Acacia nilotica extract. A thorough investigation has shown that the phytochemicals of Acacia nilotica’s hydroalcoholic extract were assessed for phenolic, flavonoid alkaloid, saponin, carbohydrate, protein, and triterpenoid compounds .The extract of Acacia nilotica contain Alkaloid in amount of 8 % , Flavonoid 6 % and saponin 2.24 %.